Comparative study to evaluate the anti-diabetic activity of commercially available extract of Tinospora cordifolia and Phyllanthus emblica in streptozocin induced diabetic rat - Pathak, Nishant; Bandyopadhyay, Arkapal; Kumar, Gyanendra; Chaurasia, Rakesh Chandra; Varma, Kachnar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes is a chronic metabolic disorder with significant socioeconomic impact on a developing country like India. Ayurvedic texts have mentioned Tinospora cordifolia (guduchi) and Phyllanthus emblica (amla) to possess antidiabetic properties. The study was conducted to evaluate the anti-diabetic activity of commercially available extract of these herbal plants in streptozocin induced diabetic rats and its comparison to standard antidiabetic drug glibenclamide. Methods: The study was carried out with albino rats of either sex weighing between 100-150 gm. All the rats were intraperitonially injected with 35 mg/kg of streptozocin in citrate buffer. Blood glucose was estimated after 1 week high fat diet and rats having blood glucose >200 mg/dl were considered diabetic and included in further study. They were divided into 6 groups of 6 rats each. Six groups were given different interventions as distilled water (which were control rats), Tinospora cordifolia extract low dose (200 mg/kg/day), Tinospora cordifolia extract high dose (400mg/kg/day), Phyllanthus emblica extract low dose (200 mg/kg/day), Phyllanthus emblica extract high dose (400 mg/kg/day) and standard drug glibenclamide (0.6 mg/kg/day). All the rats received allocated drugs for further 6 weeks. Blood glucose was measured every 2 weeks till the end of sixth weeks by glucose-oxidase method. Results: In both low as well as high dose groups, Tinospora cordifolia and Phyllanthus emblica showed significant reduction (P <0.01) in plasma glucose levels from fourth week onwards. Conclusions: Commercially available extract of Tinospora cordifolia and Phyllanthus emblica have significant anti-diabetic activity in streptozocin induced diabetic rats.